Preservice Preschool Teachers' Responses to Bullying Scenarios: The Roles of Years of Study and Empathy - Huang, Heqing; Liu, Yanchun; Chen, Yulu (Frontiers in Psychology, 2018)
The present study is aim to examine whether preservice preschool teachers’ respond differently to physical, verbal and relational bullying, and how their years of study and trait empathy related their responses. There were 242 preservice teachers in the present study. Empathy was measured with the self-report Interpersonal Reactive Index; the Bullying Attitude Questionnaire was used to assess their perceptions of incident seriousness, their sympathy toward the victim of the bullying, and their possibility to intervene in the situation. The results revealed that the participants responded most to physical bullying and least to relational bullying. Interestingly, responses to relational bullying tended to decrease during the university period. The empathy dimensions played different roles in the participants' responses to bullying, while cognitive empathy have little relationship with the participants’ responses to bullying, emotional empathy played a more complex role in the participants’ responses to bullying: empathic concerns moderated the relationship between years of study and responses to bullying, and personal distress negatively predicted the participants' responses to all types of bullying. The implications for bullying intervention and the suggestion for teacher education are discussed.